Silver nanoparticle-film based saturable absorber for passivelyQ-switched erbium-doped fiber laser (EDFL) in ring cavity configuration - Ahmad, Harith; Ruslan, N.E.; Ismail, Mohd Afiq; Ali, Z.A.; Reduan, S.A.; Lee, C.S.J.; Harun, Sulaiman Wadi (IOP Publishing, 2016)
We report a passive Q-switched erbium-doped fiber laser based on silver (Ag) nanoparticle thin-film saturable absorber (SA). The thin film was sandwiched between two fiber ferrules, which offer flexibility and easy integration into the ring cavity. Self-started and stable Q-switching is achieved at a central wavelength of 1558.7 nm; within the C-band region. The repetition rate and pulse duration shows a typical Q-switched laser profile as we increase the pump power; the repetition rate increases from 19.471-74.074 kHz while pulse duration decreases from 8.88-3.2 μs. A signal-to-noise ratio value of 35 dB was obtained at 100 mW pump power. By using a balanced twin-detector method, the modulation depth and saturation intensity of the Ag nanoparticle thin film were measured to be 31.6% and 0.54 MW cm-2 respectively. This result offers another alternative to the existing SA materials.